The Meaning of Good Faith in Article 16 of Law Number 18 of 2003 Concerning Advocates - Sugiyanto, Charisma Adilaga; Suryokumoro, Herman; Navianto , Ismail; Permadi , Iwan (Technium Social Sciences Journal, 2021)
Article 16 of Law Number 18 of 2003 states that Advocates cannot be prosecuted, either civil or criminal, in carrying out their professional duties in good faith to benefit the client’s defense in court proceedings. Elucidation of Article 16 of Law Number 18 of 2003 defines what is meant by good faith as carrying out professional duties to uphold justice based on the law to defend the interests of his clients. Then what is meant by a court session is a court session in every level of court in all areas of the judiciary. However, in reality, some of the lawyers in Indonesia, in carrying out their profession, are caught in legal problems, either in bribery or in acts of obstruction of justice. This is due to the vagueness of norms in Article 16 of Law Number 18 of 2003, especially regarding the phrase good faith. The type of research used in writing this article is normative legal research. The results of this study are the meaning of good faith in article 16 of Law Number 18 of 2003. Running the advocate profession must be based on noble values or ethical standards and always obey all the codes of ethics and legal norms. That way, an advocate can be held accountable for the profession and criminal responsibility if, in carrying out his job, the advocate does not have good faith or bad faith, which further violates criminal law and fulfills the elements of criminal responsibility.